Report on business attachment with Jardine Thompson Graham Asia Pte Ltd. - Chiu, Hsu-Kwang. (2009)
This programme served to provide an opportunity for undergraduates to gain some working experience in their respective fields of specialization. It helped the author to apply what he had learnt in his course of study to the practical situation in industry. An application of what was learnt could also enhance the course of study. It will also reinforce the knowledge that was acquired in the university.